Impacts of socioeconomic condition and season on soil contamination with zoonotic parasites from dogs’ feces, Umuarama-PR, Brazil - Letícia Coelho Araújo; Isabela Francisco Cardoso; Mayra Carraro Di Gregorio (Revista de Ciência Veterinária e Saúde Pública, 2024)
Intestinal parasitic diseases of dogs comprise a group of globally distributed and rapidly spreading illnesses that are caused by a wide range of helminths and protozoa. The lack of veterinary care of stray dogs makes them a main source of soil contamination from many zoonoses. Thus, the aim of this study was to evaluate the frequency of intestinal parasites in feces collected in public areas of Umuarama – PR, as well as the influence of socioeconomic conditions and season. One hundred fecal samples were collected (summer: n=53; winter: n=47) from 6 neighborhoods of Umuarama – PR. The samples were processed by three coproparasitological techniques: Faust; Willis; Hoffman, Pons and Janer. Six genera of parasites belonging to helminths and protozoa were found in the collected samples. Of the 100 samples analyzed, 47% were positive for one or more parasites. Ancylostoma spp was the most frequent genus found (frequency of 43%), followed by Trichuris vulpis (10%) and Giardia spp. (10%). Of the 47 positive samples, 63% presented monoparasitism, and 36% presented polyparasitism, with the most frequent association being Ancylostoma spp and Giardia spp. The season impacted the frequency of Ancylostoma spp, Cystoisospora spp, Spirocerca lupi and Balantidium coli. The economically less favored regions showed greater diversity and frequency of parasites, as well as more cases of polyparasitism. The results obtained demonstrate the necessity of efficient public policy implementation to raise awareness of the population, as well as environmental control, in order to reduce the frequency of potentially zoonotic parasites, especially in places that have lower socioeconomic status.